Effectiveness of a structured education program on blood pressure control among patients with end stage renal disease on hemodialysis / Nor Azilah Yusof - Yusof, Nor Azilah (2019)
Introduction: Structured education program enables the HD patient with ESRD to control BP through knowledge gained and compliance to fluids and salts restriction, antihypertensive drugs and HD scheduled. Objective: This study is to determine the effectiveness of a structured educational program in BP control among HD patients with ESRD at PICOMS Batu Muda, HD Unit. Methods: This is a quasi-experimental study with sixty samples were tested for BP control knowledge; BP reading and self-care behavior adherence. Purposive sampling were used and participants were divided into intervention (n=30) and control group (n=30). Participants were assessed pre-test immediately after consented in the study and one month post-test intervention. Questionnaires were distributed to participants after being provided with educational health talks, counseling and pamphlet on controlling BP. Results: High statistical significant improvements were noted in the mean and standard deviation of percent knowledge scores, BP reading and in all adherence dimensions percent score one month post intervention as compared to pre assessment scores (baseline). Participant’s knowledge has increased (Z = -4.70, p < .000). SBP showed statistically significant between the intervention group t(29)=-13.909,p<.05) and the control group t(29)= -1.729,p>.05). All four adherence scores showed statistical significant pre and post intervention, fluids restriction t(29)= 6.113,p <.05), salt restriction t(29)= 12.245,p <.05),medication adherence t(29)= 11.549,p <.05), and HD adherence t(29)= 4.267,p <.05). Conclusions: Structured education program in HD patients with ESRD leads to increased knowledge, improved BP control and increased adherence with fluids and salts restrictions, medication an HD scheduled as evidenced by decreased in the inter-dialytic weight gain, and blood pressure values. This study proved and recommended to be use for future research.